Screening maize for drought tolerance in the Guinea savanna of West and Central Africa - Badu-Apraku, Baffour; Fakorede, M.A.B.; Menkir, A.; Kamara, A.; Dapaah, S. (Springer, 2005)
Full-sib families derived from Pool 16 DT, a tropical maize ( Zea mays L.) population, were evaluated in the 1995/96 and 1997/98 dry seasons, using two sites each season in Côte d’Ivoire. In all sites, the crop was irrigated from planting to about 2 weeks before anthesis, irrigation was discontinued thereafter for the rest of the season in one site in 1995 and both sites in 1997. Irrigation was continued till maturity in the second site in 1995. The means and ranges showed that the induced stress environments produced significantly lower grain yield, fewer ears per plant (EPP) and lower grain moisture percentage than the non-stressed site. The coefficients of variation (CVs) associated with the stressed environment were consistently larger than those associated with the non-stressed environment. Similarly, the coefficients of determination (R 2 ) values were generally higher for the non-stressed than the stressed site. Only 7 families were common to the highest-yielding 20 % of the 90 families in each evaluation environment in 1995 and the 7 families were ranked differently in the stressed relative to the non-stressed environments. EPP, plant height (PHT) and ear height (EHT) had consistent positive correlation with grain yield; correlations of days to anthesis and silking date with yield were negative. The induced stress did not properly elicit the true differences among families and may, therefore, need to be modified. We are presently experimenting with a slight modification of the method by irrigating whenever the maize plants start showing signs of temporary wilting such as leaf rolling early in the day.